EKSPRESI LOKALITAS PANORAMA BENTANG KOTA BERDASARKAN ASPEK FISIK-SPASIAL DI PADUKUHAN SAMIRONO - Leonardo Devin Setiawan; Fransiskus Xaverius Budiwidodo Pangarso (Riset Arsitektur (RISA), 2022)
Abstract - Cities change by time to time physically and non-physically. The city development produces a distinctive character even in the smallest urban creature. This distinctive character does not take quickly but is slowly and full of challenges. Townscape is a visual impression of buildings arrangement, roads, and spaces those are expressed organically to form urban spaces. Therefore, a townscape that exists in an urban area is created on delevlopment or grows by unintentionally. Apart from that, the character of a townscape from one place is different from the other. The townscapes had been created and specific in each place. The literatures for this research are: 'The Concise Townscape', 'The Aesthetic Townscape', and 'Road Form and Townscape'. The three literatures describe the existence of townscape in Europe and Japan. This is the basic knowledge in townscape and how it is applied in Indonesia, especially in the city of Yogyakarta. The urban space chosen in this research is Padukuhan Samirono. Padukuhan Samirono is located in the north of Yogyakarta City and is very close to Gadjah Mada University and Negri Yogyakarta University. Padukuhan Samirono is known as an area that provides student accomodation. The community still stand fot maintaining their cultural habit such as gathering, cultural performances, and parades. This study examines the Townscape in Padukuhan Samirono. The social and cultural activities expressed their locality as seen as in its townscape. The pictorial analysis method identify the elements of townscapes wich effects the urban space. By describing the elements of urban space with 7 factors: nature elements, space organization, mass, proportion, activity, carving, and streetscape, the local expression criteria of Padukuhan Samirono’s can be formulated. Based on observations, the local expression of townscape on Samirono changes into a modern form. This research attempts to enhance people’s aprrectiation about townscape, especially townscape in Indonesia. Key Words: townscape, pictorial analysis, Samirono, Javanese, locality